Self-standing biomass carbon electrode material and application thereof in electrochemical treatment of high-salt leachate

By using a self-contained biomass carbon electrode material for electrochemical treatment, the problems of low processing capacity and possible secondary pollution in the treatment of high-salt leachate are solved, and efficient and environmentally friendly ion removal effect is achieved.

CN119683742APending Publication Date: 2025-03-25HENAN AGRICULTURAL UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411882249.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-07
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing garbage leachate treatment methods have problems such as low processing capacity, high cost, and possible secondary pollution when treating high-salt leachate.

Method used

Using the self-contained biomass carbon electrode material, the porous structure and large specific surface area of ​​the biomass wood electrode are used to adsorb and remove ions in the leachate through electrochemical adsorption/flocculation technology under low voltage conditions.

Benefits of technology

It has achieved efficient removal of chloride, COD, total nitrogen, ammonia nitrogen, calcium ions, magnesium ions, potassium ions and sodium ions in high-salt leachate, with a removal rate of up to 86% to 99%, and no by-products were generated during the process, which is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005198478890000011
    Figure HDA0005198478890000011
  • Figure HDA0005198478890000012
    Figure HDA0005198478890000012
  • Figure HDA0005198478890000021
    Figure HDA0005198478890000021
Patent Text Reader

Abstract

The invention discloses a self-standing biomass carbon electrode material and application thereof in electrochemical treatment of high-salinity leachate, and belongs to the technical field of biomass materials and high-salinity leachate treatment thereof. The preparation method comprises the following steps: adhering a layer of conductive polymer in a biomass pore channel through ultrasonic treatment and impregnation, freeze-drying, and then placing in a tubular furnace for high-temperature carbonization to prepare the self-standing biomass carbon electrode material PPY-CW. The PPY-CW material prepared by the preparation method disclosed by the invention has relatively high stability, and no metal is doped in the PPY-CW material, so that no new metal pollution is introduced in the electro-catalysis process. In addition, the PPY-CW material is applied to electrochemical treatment of high-salt leachate, and the removal rate of metal ions such as calcium, magnesium and sodium, chlorides, ammonia nitrogen and the like is high; and less flocculent precipitate is generated in the process of electrochemically treating the high-salt leachate, so that separation and recovery are facilitated. Therefore, the related technical problems in the existing landfill leachate treatment method can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

1. Technical field:

[0001] The invention belongs to the technical field of biomass materials and their use in treating high-salt leachate, and in particular relates to a self-supporting biomass carbon electrode material and its application in electrochemical treatment of high-salt leachate. 2. Background technology:

[0002] At present, the existing methods for treating landfill leachate include: coagulation and sedimentation, ion exchange technology, electrosorption technology and electrochemical treatment. Coagulation and sedimentation adds chemical agents to wastewater to make tiny particles and colloidal particles in the water form larger flocs. The flocs have strong adsorption and can adsorb soluble substances and some bacteria in the water. After adsorption, the volume and weight of the flocs increase, so they sink to the bottom of the water, thereby achieving separation from the water. Ion exchange technology usually uses ion exchange resins or synthetic polymer materials to achieve the purpose of separating, exchanging and purifying ions in water. Electrochemical treatment technology can not only have a coagulation and precipitation effect on colloidal impurities and suspended matter, but also remove a variety of pollutants in water through the redox effect of electrodes. Electrosorption technology uses the phenomenon that the surface of charged electrodes adsorbs ions and charged particles in water, so that dissolved salts and other charged substances in water are enriched and concentrated on the surface of the electrode.

[0003] Reverse osmosis is an energy-saving process based on a semipermeable membrane, but the membrane is easily contaminated and replacing the membrane will result in excessive costs. CDI is a new process based on the electrical absorption of salt ions in the electrical double layer, but its treatment capacity is low and it is only suitable for low-salinity brackish water because high concentrations of salt always cause serious co-existing ion effects. For ion exchange technology, when the leachate flows through the ion exchange resin at a specific height, the resin will adsorb metal ions or other impurities in the leachate, and the ion exchange reaction is reversible. After a period of use, the resin can be regenerated by acid, alkali or other regeneration agents to restore its exchange capacity. Although this technology has high treatment efficiency and can be reused, the regeneration of the resin requires additional chemicals, which may cause secondary pollution in some cases.

[0004] With the continuous development of cities and the strengthening of people's environmental awareness, the output of wastewater has increased year by year. This waste contains a large number of toxic and harmful substances such as pathogens. If it is not properly treated and disposed of, it will cause major environmental risks and even harm human health. In the context of global environmental protection and sustainable development, the treatment of leachate generated by urban landfills has become an important issue and challenge.

[0005] The biomass wood catalyst electrode has a natural porous structure, which is conducive to the adsorption and removal of ions in the leachate; compared with traditional catalyst electrodes, the wood catalyst electrode is widely available, renewable, and has a low production cost, which conforms to the concept of green and sustainable development; the porous structure of the wood catalyst electrode gives it a large specific surface area and provides more active sites. The use of biomass wood catalyst electrodes for electrochemical treatment of ions in leachate is a technology that is easy to operate, has low pollution, high energy utilization, and no by-products are produced during the entire process, which is environmentally friendly. Therefore, the present invention applies the prepared self-supporting biomass carbon electrode material to the electrochemical treatment of high-salt leachate, and the use of porous biomass catalyst electrodes to electrochemically treat high-salt garbage leachate is a highly feasible waste liquid treatment technology. 3. Summary of the invention:

[0006] The technical problem to be solved by the present invention is: according to the status of the current existing methods for treating landfill leachate and the problems existing therein, the present invention provides a self-supporting biomass carbon electrode material and its application in treating high-salt leachate. The present invention applies the self-made self-supporting biomass carbon electrode material to the treatment of high-salt leachate, and uses the porous structure and large specific surface area of ​​the biomass wood electrode through electrochemical adsorption / flocculation technology. Under the condition of applying a low voltage, the electrode is immersed in the leachate, and through the electrosorption effect, the ions in the leachate enter the electrode pores, or form floccules between the electrodes, thereby achieving the purpose of desalination or ion removal, so as to solve the problems existing in the prior art.

[0007] In order to solve the above problems, the technical solution adopted by the present invention is:

[0008] The present invention provides a self-supporting biomass carbon electrode material, which comprises a birch substrate and a conductive polymer growth part. The preparation method comprises the following steps:

[0009] a. dissolving ammonium persulfate in pure water to prepare an ammonium persulfate solution;

[0010] b. dissolving pyrrole in concentrated sulfuric acid (concentration is 98%) to obtain pyrrole sulfuric acid solution;

[0011] c. slowly pouring the obtained pyrrole sulfuric acid solution into the obtained ammonium persulfate solution to obtain a mixed solution; and then immersing the cut birch wood blocks into the mixed solution for ultrasonic treatment;

[0012] d. After ultrasonic treatment, place the birch solution in an ice water bath;

[0013] e. After the ice water bath, take out the birch and place it in a plastic petri dish for freeze drying;

[0014] f. The freeze-dried birch is placed in a tubular furnace for high-temperature carbonization, and the temperature is lowered after carbonization to obtain a self-supporting biomass carbon electrode material, namely, PPY-CW material.

[0015] According to the above-mentioned self-supporting biomass carbon electrode material, the mass percentage concentration of the ammonium persulfate solution obtained in step a is 8-15%.

[0016] According to the above-mentioned self-supporting biomass carbon electrode material, when the pyrrole is dissolved in concentrated sulfuric acid in step b, the volume ratio of pyrrole to concentrated sulfuric acid is 1:10-20.

[0017] According to the above-mentioned self-supporting biomass carbon electrode material, the volume ratio of the pyrrole sulfuric acid solution and the ammonium persulfate solution added in step c is 1:1-3.

[0018] According to the above-mentioned self-supporting biomass carbon electrode material, the specifications of the birch block in step c are 6mm×15mm×25mm; during the ultrasonic treatment, the ultrasonic treatment time is controlled to be 60min.

[0019] According to the above-mentioned self-supporting biomass carbon electrode material, the ice water bath time in step d is 6 to 10 hours;

[0020] The specific process of freeze drying in step e is: first freeze the sample in a freeze dryer to a temperature below -40°C, and then vacuum dry the sample to room temperature.

[0021] According to the above-mentioned self-supporting biomass carbon electrode material, the specific process of high-temperature carbonization in step f is: after the birch is placed in a tubular furnace, under nitrogen conditions, the temperature is raised to 350°C at a rate of 0.5°C / min, and maintained at 350°C for 3 hours; then the temperature is raised to 1000°C at a rate of 1°C / min and maintained for 2 hours; finally, the temperature is lowered to room temperature; the nitrogen flow rate is 0.3~0.5L / min.

[0022] In addition, a use of the self-supporting biomass carbon electrode material in electrochemical treatment of high-salt leachate is provided.

[0023] According to the above-mentioned application of the self-supporting biomass carbon electrode material in the electrochemical treatment of high-salt leachate, during the application, a redox reaction occurs in the double electrolytic cell to carry out ion transfer, the high-salt leachate at the working electrode forms an alkaline solution, and the high-salt leachate at the counter electrode becomes an acidic solution; in the single electrolytic cell, the self-supporting biomass carbon electrode material is used as the working electrode and the counter electrode, and a voltage is applied to the electrodes through an electrochemical workstation, so that the cations in the leachate are transferred to the negative electrode, and the anions are transferred to the positive electrode, adsorbed in the pores of the electrodes, or flocculation is formed between the electrodes, thereby achieving the purpose of deionization (it has good stability and ion removal rate during the electrochemical treatment of high-salt leachate).

[0024] According to the above-mentioned application of the self-supporting biomass carbon electrode material in the electrochemical treatment of high-salt leachate, in the high-salt leachate, according to the dual-electrode system, with PPY-CW as the counter electrode and the working electrode, an electrolysis is first carried out in a dual electrolytic cell; then the electrolytes on both sides are subjected to a secondary electrolysis in a single electrolytic cell to test the electrocatalytic activity and stability of PPY-CW, in which both the working electrode and the counter electrode are made of PPY-CW materials.

[0025] Before the high-salt leachate is treated, the contents of chloride, COD, total nitrogen, ammonia nitrogen, calcium ion, magnesium ion, potassium ion and sodium ion are 5520 mg / L, 1383 mg / L, 612 mg / L, 402 mg / L, 117.6 mg / L, 108.9 mg / L, 2226 mg / L and 5490 mg / L respectively. After being treated with the self-supporting biomass carbon electrode material of the present invention, the contents of chloride, COD, total nitrogen, ammonia nitrogen, calcium ion, magnesium ion, potassium ion and sodium ion in the high-salt leachate are 760 mg / L, 410 mg / L, 41.75 mg / L, 2.75 mg / L, 5.49 mg / L, 0.9 mg / L, 57.3 mg / L and 222 mg / L respectively.

[0026] As a result, the removal rate of chloride is as high as 86%, the removal rate of COD is as high as 70%, the removal rate of total nitrogen is as high as 93%, the removal rate of ammonia nitrogen is as high as 99%, the removal rate of calcium ions is as high as 95.3%, the removal rate of magnesium ions is as high as 99%, the removal rate of potassium ions is as high as 97%, and the removal rate of sodium ions is as high as 95.9%.

[0027] In the technical solution of the present invention, the biomass is selected as the substrate of birch, a dense and non-collapsed large-pore hardwood. The porous structure of the wood provides a large specific surface area, providing sufficient space for the attachment of the conductive polymer. The birch block is immersed in a mixed solution and subjected to ultrasound and ice-water bath treatment, so that the polypyrrole can enter the pores of the birch and be evenly distributed, which is conducive to the next step. The freeze-dried birch block is placed in a tubular furnace under nitrogen conditions throughout the process, so that the birch substrate is carbonized and the conductivity is increased; at high temperature, the polypyrrole undergoes structural reorganization on the birch pore wall, making the catalyst electrode harder.

[0028] The positive beneficial effects of the present invention are:

[0029] 1. The self-supporting biomass carbon electrode material prepared by the present invention is applied to the electrochemical treatment of high-salt leachate. The pore structure of the biomass carbon electrode does not change. After the system runs for 100 hours, the biomass carbon material remains stable. During the electrochemical treatment of high-salt leachate, a small amount of flocculation occurs in the electrolyte around the working electrode and agglomerates and falls off. It is clearly observed that the color of the water becomes lighter.

[0030] 2. The self-supporting biomass carbon electrode material prepared by the present invention is applied to the electrochemical treatment of high-salt leachate, with a chloride removal rate of up to 86%, a COD removal rate of up to 70%, a total nitrogen removal rate of up to 93%, ammonia nitrogen removal rate of up to 99%, a calcium ion removal rate of up to 95.3%, a magnesium ion removal rate of up to 99%, a potassium ion removal rate of up to 97%, and a sodium ion removal rate of up to 95.9%.

[0031] 3. The self-supporting biomass carbon electrode material prepared by the present invention is applied to the electrochemical treatment of high-salt leachate. The biomass carbon electrode is circulated in the high-salt leachate, and the results of each cycle are analyzed. It is found that the biomass carbon electrode has good stability.

[0032] 4. The self-supporting biomass carbon electrode material prepared by the present invention has no metal doping and will not introduce new metal pollution during the electrocatalytic process.

[0033] In summary, the PPY-CW material prepared by the present invention has high stability, and there is no metal doping in the PPY-CW material, and no new metal pollution will be introduced during the electrocatalytic process. In addition, the PPY-CW material of the present invention is used in the electrochemical treatment of high-salt leachate, and calcium, magnesium metal ions, chlorides, ammonia nitrogen, etc. have a high removal rate; there is less flocculation precipitation during the electrochemical treatment of high-salt leachate, which is conducive to separation and recovery. Therefore, the present invention can effectively solve the technical problems existing in the existing landfill leachate treatment methods. 4. Description of the drawings:

[0034] Figure 1 It is a schematic diagram of the synthesis process of the self-supporting biomass carbon electrode material of the present invention;

[0035] During the synthesis process, the immersion time is 6-10 hours, that is, a short time will not cause the wood to stick together or break during the calcination process. High-temperature carbonization is conducive to the formation of a solid graphite layer, which is beneficial to the stability of the material.

[0036] Figure 2 It is a schematic diagram of an experimental device for applying the self-supporting biomass carbon electrode material of the present invention to the electrochemical treatment of high-salt leachate;

[0037] Figure 2 The double electrolytic cell on the left (end of the test) is connected to the H + The single electrolytic cell is a device for performing secondary electrolysis on the counter electrode side.

[0038] Figure 3 This is an X-ray photoelectron spectrum analysis diagram of the PPY-CW material prepared by the present invention;

[0039] Figure 3In the study, X-ray photoelectron spectroscopy (XPS) was used to illustrate the elemental composition and distribution of PPY-CW, revealing subtle differences in their N-doped structures before and after electrochemical reconstruction. Pyrrolic N became the main species after 106 hours, and a peak of nitrate appeared.

[0040] Figure 4 This is a transmission electron microscope image of the PPY-CW material prepared in the present invention;

[0041] Depend on Figure 4 The presence of graphite carbon layers can be observed, which is consistent with the Figure 3 be consistent.

[0042] Figure 5 The LSV diagram of the PPY-CW material prepared by the present invention used as an electrode in landfill leachate;

[0043] Depend on Figure 5 The highest voltage window that the self-supporting biomass carbon electrode can withstand can be determined through the changing relationship between voltage and current.

[0044] Figure 6 It diagram of the PPY-CW catalyst electrode of the present invention when a voltage of -3V is applied to the electrode electrolyte in the secondary electrolysis after the primary electrolysis of landfill leachate;

[0045] Depend on Figure 6 It can be seen that the current tends to be stable after 4 hours.

[0046] Figure 7 It diagram of the application of -2V voltage in the process of using the PPY-CW material prepared by the present invention as an electrode in landfill leachate;

[0047] Depend on Figure 7 It can be seen that the current gradually increases during the reaction, indicating that the effect of the electrode material is getting better and better.

[0048] Figure 8 This is a flocculation diagram of the PPY-CW material prepared by the present invention as an electrode after electrochemical reaction in the leachate;

[0049] Depend on Figure 8 It can be seen that the reaction produces little flocculation, which is beneficial for separation after electrochemical treatment of high-salt leachate.

[0050] Fig. 9 This is the elemental analysis diagram of flocculation after the PPY-CW material prepared in the present invention is used as a catalyst electrode for electrochemical reaction in the leachate.

[0051] Depend on Fig. 9 It can be shown that some metal ions in landfill leachate were removed by electrocoagulation. V. Specific implementation methods:

[0052] In order to make the purpose and implementation methods of the present invention clearer, the technical solution of the present invention is clearly and completely described below in combination with specific embodiments and drawings. Obviously, the described embodiments are only partial embodiments of the technical solution of the present invention, rather than all embodiments.

[0053] Embodiment 1:

[0054] The self-supporting biomass carbon electrode material of the present invention comprises a birch substrate and a conductive polymer growth part. The detailed steps of the preparation method are as follows:

[0055] a. Dissolve 11.4 g of ammonium persulfate in 100 mL of pure water to prepare an ammonium persulfate solution;

[0056] b. Dissolve 3.45 mL of pyrrole in 50 mL of concentrated sulfuric acid (98%) to obtain a pyrrole sulfuric acid solution;

[0057] c. slowly pouring the obtained pyrrole sulfuric acid solution into the obtained ammonium persulfate solution to obtain a mixed solution; then immersing the cut birch blocks of 6 mm×15 mm×25 mm into the mixed solution and performing ultrasonic treatment for 60 minutes;

[0058] d. After ultrasonic treatment, the birch solution was placed in an ice-water bath for 6 h;

[0059] e. After the ice water bath, take out the birch and put it into a plastic culture dish, then put it into a freeze dryer and freeze it to below -40°C, then vacuum dry it until the sample temperature reaches room temperature;

[0060] f. Put the freeze-dried birch into a tube furnace for high-temperature carbonization, and cool it down after carbonization to obtain a self-supporting biomass carbon electrode material, namely PPY-CW;

[0061] The specific process of high-temperature carbonization is as follows: after the birch is placed in a tubular furnace, the temperature is raised to 350°C at a rate of 0.5°C / min under nitrogen conditions, and maintained at 350°C for 3 hours; then the temperature is raised to 1000°C at a rate of 1°C / min and maintained for 2 hours; finally, the temperature is lowered to room temperature; the nitrogen flow rate is controlled to be 0.3-0.5L / min.

[0062] Application examples of the self-supporting biomass carbon electrode material of the present invention in electrochemical treatment of high-salt leachate:

[0063] Application Example 1:

[0064] The self-supporting biomass carbon electrode material prepared in Example 1 of the present invention was used as the working electrode and the counter electrode. The high-salt leachate was first treated in a double electrolytic cell at a voltage of -3 V for 4 hours. Then, the electrolyte containing the counter electrode was electrolyzed in a single electrolytic cell at -3 V for 12 hours using PPY-CW as the working electrode and the counter electrode.

[0065] Before the high-salt leachate is treated, the contents of chloride, COD, total nitrogen, ammonia nitrogen, calcium ion, magnesium ion, potassium ion and sodium ion are 5520 mg / L, 1383 mg / L, 612 mg / L, 402 mg / L, 117.6 mg / L, 108.9 mg / L, 2226 mg / L and 5490 mg / L respectively. After being treated with the self-supporting biomass carbon electrode material of the present invention, the contents of chloride, COD, total nitrogen, ammonia nitrogen, calcium ion, magnesium ion, potassium ion and sodium ion in the high-salt leachate are 760 mg / L, 410 mg / L, 41.75 mg / L, 2.75 mg / L, 5.49 mg / L, 0.9 mg / L, 57.3 mg / L and 222 mg / L respectively. The removal rate of chloride is as high as 86%, the removal rate of COD is as high as 70%, the removal rate of total nitrogen is as high as 93%, the removal rate of ammonia nitrogen is as high as 99%, the removal rate of calcium ions is as high as 95.3%, the removal rate of magnesium ions is as high as 99%, the removal rate of potassium ions is as high as 97%, and the removal rate of sodium ions is as high as 95.9%.

[0066] The mechanism of the self-supporting biomass carbon electrode material of the present invention when used in the electrochemical treatment of high-salt leachate is as follows: an oxidation-reduction reaction occurs in a double electrolytic cell to carry out ion transfer, the high-salt leachate at the working electrode forms an alkaline solution, and the high-salt leachate at the counter electrode becomes an acidic solution; in a single electrolytic cell, the self-supporting biomass carbon electrode material is used as a working electrode and a counter electrode, and a voltage is applied to the electrodes through an electrochemical workstation, so that cations in the leachate are transferred to the negative electrode, and anions are transferred to the positive electrode, adsorbed in the pores of the electrodes, or flocculation is formed between the electrodes, thereby achieving the purpose of deionization (it has good stability and ion removal rate during the electrochemical treatment of high-salt leachate).

[0067] Attached Figure 4 This is a transmission electron microscope image of the PPY-CW material prepared in the present invention; Figure 4 As shown, under the transmission electron microscope image, it can be seen that the PPY-CW material prepared by the present invention has a lattice at 0.331nm.

[0068] In the process of using the self-supporting biomass carbon electrode material of the present invention in treating high-salt leachate, the electrode is reconstructed inside, such as the attached Figure 3 As shown, graphitic N is converted into pyrrolic N and nitrate is generated.

[0069] The self-supporting biomass carbon electrode material of the present invention has good stability and high current density in the process of treating high-salt leachate in Example 1. Figure 5 and attached Figure 6 shown.

[0070] In the process of using the self-supporting biomass carbon electrode material of the present invention in treating high-salt leachate, flocculation occurs, such as Figure 8 Scanning electron microscopy and elemental analysis of flocculation showed the presence of metal precipitation such as calcium and magnesium.

Claims

1. A self-supporting biomass carbon electrode material, characterized in that: The self-supporting biomass carbon electrode material comprises a birch substrate and a conductive polymer growth part, and the preparation method comprises the following steps: a. dissolving ammonium persulfate in pure water to prepare an ammonium persulfate solution; b. dissolving pyrrole in concentrated sulfuric acid to obtain a pyrrole sulfuric acid solution; c. slowly pouring the obtained pyrrole sulfuric acid solution into the obtained ammonium persulfate solution to obtain a mixed solution; and then immersing the cut birch wood blocks into the mixed solution for ultrasonic treatment; d. After ultrasonic treatment, place the birch solution in an ice water bath; e. After the ice water bath, take out the birch and place it in a plastic petri dish for freeze drying; f. The freeze-dried birch is placed in a tubular furnace for high-temperature carbonization, and the temperature is lowered after carbonization to obtain a self-supporting biomass carbon electrode material, namely, PPY-CW material.

2. The self-supporting biomass carbon electrode material according to claim 1, characterized in that: The mass percentage concentration of the ammonium persulfate solution obtained in step a is 8-15%.

3. The self-supporting biomass carbon electrode material according to claim 1, characterized in that: When the pyrrole is dissolved in concentrated sulfuric acid in step b, the volume ratio of pyrrole to concentrated sulfuric acid is 1:10-20.

4. The self-supporting biomass carbon electrode material according to claim 1, characterized in that: In step c, the volume ratio of the pyrrole sulfuric acid solution to the ammonium persulfate solution is 1:1-3.

5. The self-supporting biomass carbon electrode material according to claim 1, characterized in that: The birch block in step c has a specification of 6 mm×15 mm×25 mm; during the ultrasonic treatment, the ultrasonic treatment time is controlled to be 60 min.

6. The self-supporting biomass carbon electrode material according to claim 1, characterized in that: The ice water bath time in step d is 6 to 10 hours; The specific process of freeze drying in step e is: first freeze the sample in a freeze dryer to a temperature below -40°C, and then vacuum dry the sample to room temperature.

7. The self-supporting biomass carbon electrode material according to claim 1, characterized in that: The specific process of high-temperature carbonization in step f is as follows: after the birch is placed in a tubular furnace, the temperature is raised to 350°C at a rate of 0.5°C / min under nitrogen conditions, and maintained at 350°C for 3 hours; then the temperature is raised to 1000°C at a rate of 1°C / min and maintained for 2 hours; finally, the temperature is lowered to room temperature; the nitrogen flow rate is 0.3-0.5L / min.

8. Use of the self-supporting biomass carbon electrode material according to claim 1 in electrochemical treatment of high-salt leachate.

9. The use of the self-supporting biomass carbon electrode material in electrochemical treatment of high-salt leachate according to claim 8, characterized in that: During the application, a redox reaction occurs in the double electrolytic cell to transfer ions, the high-salt leachate at the working electrode forms an alkaline solution, and the high-salt leachate at the counter electrode becomes an acidic solution; In a single electrolytic cell, the self-supporting biomass carbon electrode material is used as the working electrode and the counter electrode. Voltage is applied to the electrodes through an electrochemical workstation, so that the cations in the leachate are transferred to the negative electrode and the anions are transferred to the positive electrode. They are adsorbed in the pores of the electrodes or form flocculation between the electrodes, thereby achieving the purpose of deionization.

10. The use of the self-supporting biomass carbon electrode material in electrochemical treatment of high-salt leachate according to claim 9, characterized in that: In high-salt leachate, according to the dual-electrode system, PPY-CW was used as the counter electrode and the working electrode, and electrolysis was first carried out in a dual electrolytic cell; then the electrolytes on both sides were subjected to secondary electrolysis in a single electrolytic cell to test the electrocatalytic activity and stability of PPY-CW. Both the working electrode and the counter electrode in the single electrolytic cell were made of PPY-CW materials.

Citation Information

Patent Citations

  • Method for preparing eggshell membrane / graphene / polymer composite flexible supercapacitor

    CN108962630A

  • Porous carbon composite material for constructing polypyrrole in plant cells as well as preparation method and application of porous carbon composite material

    CN116031080A

  • Copper-loaded balsa wood-based self-supporting carbon electrode as well as preparation method and application thereof

    CN118538546A

  • Method for production of activated carbon for electrical engineering purposes

    RU2223911C1

  • High specific capacitance solid state supercapacitor and method of manufacture

    US20230335346A1